2020
DOI: 10.1161/hypertensionaha.120.15504
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Protects Hyperandrogenemic Female Rats From Postmenopausal Hypertension

Abstract: Polycystic ovary syndrome, the most common endocrine disorder in women of reproductive age, is characterized by hyperandrogenemia, obesity, insulin resistance, and elevated blood pressure. However, few studies have focused on the consequences of pregnancy on postmenopausal cardiovascular disease and hypertension in polycystic ovary syndrome women. In hyperandrogenemic female (HAF) rats, the hypothesis was tested that previous pregnancy protects against age-related hypertension. Rats were implanted with dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…HAF rats have elevated blood pressure prior to pregnancy (Yanes et al, 2011), as has also be reported in PCOS women (Christakou & Diamanti-Kandarakis, 2008). We have also shown that the higher body weights prepregnancy in HAF rats remain so 48 h postpartum, but comparisons of percentage weight gains per body weight from pre to post-pregnancy are similar between the control and HAF dams (Shawky et al, 2020). The numbers of pups per litter were also similar between HAF and control pregnancies (Shawky et al, 2020).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…HAF rats have elevated blood pressure prior to pregnancy (Yanes et al, 2011), as has also be reported in PCOS women (Christakou & Diamanti-Kandarakis, 2008). We have also shown that the higher body weights prepregnancy in HAF rats remain so 48 h postpartum, but comparisons of percentage weight gains per body weight from pre to post-pregnancy are similar between the control and HAF dams (Shawky et al, 2020). The numbers of pups per litter were also similar between HAF and control pregnancies (Shawky et al, 2020).…”
Section: Discussionsupporting
confidence: 78%
“…As mentioned above, we have shown previously that the numbers of pups per litter were similar between control and HAF offspring, but the birth weights of male and female HAF offspring were lower than those for control offspring (Shawky et al, 2020). As shown in Figure 1A, body weights remained lower in HAF males until PND 4, when they became similar to body weight in controls, and remained similar up to 8 weeks of age (Figure 1b,c).…”
Section: Characteristics Of Offspringsupporting
confidence: 71%
See 3 more Smart Citations